Seleção Otimizada de Enlaces Instáveis em Redes de Comunicação ATN/IPS - Sernagiotto, Marco Aurelio [UNIFESP] (2019)
The aeronautical communications in the new concept of ATN-BR (Aeronautical Telecommunication Network -- Brazil) bring a new communication model, exclusively digital. As a result, network management becomes essential to ensure the continuity of communications. In this context, the heterogeneous network selection techniques cited in the literature are a way to perform the datalink selection based on criteria that meet the requirements of communication services and users of this aeronautical network. The aim of this document is to present an integrated optimization model to select aeronautical network links, maximizing network usage while minimizing the difference in capacity utilization between datalinks (load balancing). To achieve this goal, multicriteria evaluation techniques are combined with a multiobjective optimization method. For the analysis of subjective criteria the AHP method (Analytic Hierarchy Process) is used and for the objective criteria, the utility functions are used. The criteria are combined with the SAW (Simple Additive Weighting) compensatory multicriteria method to evaluate possible datalink-packet combinations. And ɛ-Restricted multiobjective optimization provides Pareto-optimal boundary values as the balancing levels (ɛ) are set for the network. The datalink selection problem is approached through a case study, with data generated based on the real ATN-Br data. The results obtained in this case study indicate that there is a trade-off value that maximizes profit use and minimizes the difference in link usage (difference between available bandwidth used rates) without causing an increase in packet loss. Thus, the presented solution offers network managers a reference for optimized operation of ATN-Br, ensuring the continuity of the most critical (priority) communications, even in scenarios of link instability.